Cost Analysis of the Boiler Unit of Coal Power Units Depending on the Initial Steam Pressure and the Availability оf Flue Gas Purification Systems - I. S. Sadkin; A. P. Shipitsina; P. A. Shchinnikov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
When designing power plants of a new type or equipping them with new generation equipment, the problem of estimating capital investments is solved with the uncertainty of information on its cost. The lack of reliable methods suitable for use in engineering setting complicates decision-making on the technical development of power units and thermal power plants. When evaluating investments in the equipment of power plant units, it is convenient to use continuous functions. Their use makes it possible to carry out the analysis without cost restrictions. The article proposes a method for estimating capital investments in the boiler island of power units of power plants based on a power parametric function. The method includes an assessment of the cost of a boiler unit with fuel preparation systems within the boiler shop, draught and blast. A specific feature of the method is that the cost of the boiler includes the cost of flue gas purification systems from harmful combustion products in the form of ash, sulfur oxides and nitrogen oxides. The method was developed in an engineering setting. The methodological section demonstrates the performance of the method in assessing capital investments in a boiler island in comparison with the same indicator for the EU countries, the USA and China. When discussing the results of the study, it was found that capital investments in a coal-fired boiler with flue gas purification systems is in the range of US$ 25–200 million, depending on the power and initial steam parameters. The share of the cost of environmental flue gas purification systems is 28–50 % of the total cost of the boiler unit. It is demonstrated that the design of coal-fired power units with flue gas purification systems for supercritical parameters with a capacity of less than 300 MW is inefficient due to low competitiveness in terms of specific investments in the boiler.